Design of Integrated Polarizer to Evaluate Quality of Cooking Oil Based on the Fluorescence Polarization Method - Heri Sugito; Ketut Sofjan Firdausi (Journal of Physics and Its Applications, 2018)
An integrated polarizer was designed as an alternative test tool to evaluate quality of cooking oils. Integrated Polarizer was composed of light source with wavelength of 532 ± 10 nm, polarizer, analyser, cuvette, electrodes, and high voltage source. In this research, the tool works based on the fluorescence polarization method. Measurements were made by observing the fluorescence polarization angle changes that occur and by applying an external electric field at the samples using high voltage of 0-9 kV in the parallel plate. The results show that the expired cooking oil has a greater polarization angle than the edible cooking oil. The results also show that the change in the polarization angle will increase in proportion to the increase of the heating time. The condition of saturated fatty acids in each sample has an effect on the change of polarization angle.